Influence of symmetric perturbations on optical properties of molecular nanofilms - Siniša M. Vučenović; Jovan P. Šetrajčić (Zaštita Materijala)
In this paper we have calculated optical changes under the influence of the boundary conditions in molecular crystalline nanostructured films. We have used theoretical model with the adjusted Greens functions, and using numerical calculations we have calculated dispersion law for excitons, and their spatial distribution along the boundary planes. In this procedure we limited ourselves on case with symmetrically perturbed conditions, and showed that the primary optical properties significantly change just in these planes where perturbations have main influence. We have determined coefficient of absorption, reflection, transparency and refraction on the base of real and imaginary part of the relative dielectric permittivity. Especially interesting case is that those structures show significantly contribution of the reflective and transparent radiation in the IR part of the spectra, while the same material in bulk almost completely absorb radiation in this part of spectra.